Odontogenic Facial Cellulitis in Children: Review Article - Abdullah S. Al-Mushayt; Zeinab E. Darwish; Narmin S. Helal (Journal of King Abdulaziz University: Medical Sciences, 2023)
Facial cellulitis is a common clinical problem in pediatric patients. It is an infection of the skin that causes pain, swelling, and redness on the face. Additional symptoms include fever, chills, swollenness and tender tongue. Although the disease itself is not serious, its important to get it treated promptly because it can cause serious complications. The main objective of this article is to review the literature and to emphasize the importance of establishing guidelines on the proper management of this condition. Diagnosis of facial cellulitis starts by history, overall assessment and local examination. In addition, panoramic radiograph, magnetic resonance imaging, ultrasonography and computed tomography could be considered as effective methods of detecting such cases. Hospital admission and the use of antibiotic should not always be the first management, since it is guarded by several limits. Simple management guidelines should include two major steps: removal of the cause and local drainage, and debridement. Previous studies found faster resolution of infection and less use of antibiotic is associated with early surgical drainage. Analgesics and nutritional support are mandatory. Although, the present review gives some high light on facial cellulitis in pediatric dentistry, more systematic reviews of literature are still needed in this point of interest.